Development and Psychometric Validation of an Instrument to Identify Barriers to Self-Care Among Spanish Patients With Type 2 Diabetes on the Basis of Theory of Planned Behavior - Caro-Bautista, Jorge; Espinar-Toledo, Milagrosa; Villa-Estrada, Francisca; Lupiáñez-Pérez, Inmaculada; Kaknani-Uttumchandani, Shakira; García-Mayor, Silvia; Salas-Samper, Felipe; Morales-Asencio, José-Miguel (Value in health, 2019)
Several instruments are available to evaluate barriers to self-care in people with type 2 diabetes, but with significant psychometric weaknesses and poor theoretical background. To develop and psychometrically validate a questionnaire to identify barriers to self-care in this population on the basis of the theory of planned behavior. The study was carried out in 15 primary healthcare centers belonging to the Public Health Care System in Andalusia (Spain). After content validity was confirmed, an initial pilot study was undertaken (n = 54) and the model was evaluated in 2 samples of 205 subjects each to test its configural and metric invariance by confirmatory factor analysis. Internal consistency, test-retest reliability, criterion validity, and interpretability were carried out following COSMIN standards. A 4-factor instrument (intention, subjective norms, perceived control, and attitudes) with 15 items was obtained with a good fit: goodness-of-fit index = 0.92, comparative fit index = 0.93, and root mean square error of approximation = 0.043 (90% confidence interval 0.034-0.052). Cronbach α was 0.78, and test-retest reliability was adequate (intraclass correlation coefficient 0.73; P < .0001). The instrument revealed an adequate criterion validity depending on the treatment complexity and level of metabolic control. Thus, participants with poor self-care scores were more likely to suffer from diabetes-related complications (odds ratio 1.91; 95% confidence interval 1.15-3.1). A theory-driven instrument is suitable for its use with Spanish people with type 2 diabetes to assess their self-care needs and make tailored recommendations for lifestyle modifications on the basis of their behavioral determinants. •Numerous questionnaires are used to evaluate self-care barriers/behaviors, either self-efficacy or self-management, in a type 2 diabetic population before the implementation of an educational program, as well as to evaluate its impact. Nevertheless, these instruments present important methodological weaknesses, and most are not based on a solid theoretical framework.•The EBADE Questionnaire based on the theory of planned behavior has managed to group in 15 items relative to self-care areas in type 2 diabetes to its 4 constructs (behavioral beliefs, perceived control behavior, subjective norms, and intent behavior). In turn, a valid and reliable solution has been obtained, with an adequate adjustment in the confirmatory factor analysis and that relates the presence of self-care barriers with greater chances of suffering diabetes complications in a Spanish diabetic population.•This instrument raises the possibility of changing the model of educational attention to people with type 2 diabetes, basing it on grouping activities on behavioral constructs rather than on classic self-care areas, and carrying out tailored interventions to the identified needs.